Heterogeneity across emerging market central bank reaction functions - Mesut Turkay (Central Bank Review (CBR), 2017)
The purpose of this study is to analyze monetary policy reaction functions of inflation targeting emerging market economies. Heterogeneity across central bank behavior is modelled using dynamic common correlated effects estimator in a panel data framework of 15 countries. The empirical method allows us to obtain country specific coefficients and shows differences across central bank reaction functions. Model results imply that central banks behave according to an extended Taylor rule and respond to deviation of inflation from the target, output gap, real exchange rate and external financial conditions. The study finds that emerging market central banks consider not only price stability, but also financial stability in setting of interest rates.
Keywords: 330; Reaction function; Dynamic common correlated effects; Heterogeneity